A review on the strategic planning of tourism enterprises in the post-epidemic era - Huo, MengJie; Li, ShuYu; Yan, JingXian; Zhang, XiaoYi; Wu, JinMing; Abdul Aziz, Faieza (IJISRT, 2023)
The Covid-19 has been effectively controlled and epidemic prevention and control has entered normalization. However, in the post-epidemic era, many tourism enterprises still face many challenges in their development. Most of the current research focuses on the analysis of the impact of the epidemic on tourism industry, and less on the strategic planning of tourism enterprises in the post-epidemic era. This paper reviews the impact of the epidemic crisis on tourism enterprises and summarizes their response experience, so as to propose corresponding strategic planning and promote the high-quality development of tourism enterprises.